The Impact of Information Gap Activities on Young EFL Learners' Oral Fluency - Ramón Antonio Ortiz-Neira (Universidad Nacional de Colombia, 2019)
This study adopted a mixed method approach with an action research design. The aim was to determine the impact of information gap activities on young English as a foreign language learners' oral fluency. Information gap activities were based on the communicative approach as well as on task-based learning. Twenty-three eighth graders participated in this action research. The students were immersed in a multicultural and at-risk context in a public high school in southern Chile. Their English-speaking level fluctuated between A1 and A2. The technique was applied over the course of a semester (ten weeks). Data were collected by applying a pre-test, post-test, and focus group questionnaire. Results suggest an improvement in oral fluency and a positive perception of the technique used during the intervention.